AYAT DAN HADIST TENTANG PERCERAIAN - Habibulloh, Muh.; Hernas, Erika Putri; Nur'aini, Intan; Zakariya, Rizki (Dahzain Nur, 2023)
Marriage is a worship that is loved by Allah SWT, but in carrying it out, every marriage will experience problems. When the problem cannot be resolved, the last resort that every couple will take is divorce (talak). This journal aims to explore the hadiths of the Prophet SAW. relating to divorce, outlining the law of divorce according to the opinion of the theologian.